2009
DOI: 10.1002/pro.27
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of domain‐swapped STE20 OSR1 kinase domain

Abstract: OSR1 (oxidative stress-responsive-1) and SPAK (Ste20/Sps1-related proline/alanine-rich kinase) belong to the GCK-VI subfamily of Ste20 group kinases. OSR1 and SPAK are key regulators of NKCCs (Na2 cotransporters) and activated by WNK family members (with-no-lysine kinase), mutations of which are known to cause Gordon syndrome, an autosomal dominant form of inherited hypertension. The crystal structure of OSR1 kinase domain has been solved at 2.25 Å . OSR1 forms a domain-swapped dimer in an inactive conformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
71
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 55 publications
6
71
0
Order By: Relevance
“…Such highly coordinated interactions likely reduce the mobility of the loop compared with its unmodified state and can only be achieved by a phosphorylated residue, perhaps explaining why the TBK1 S172E phosphomimetic mutant shows decreased activity compared with the wild-type enzyme (20). The conformational change nucleated by the phosphorylation of S172 further propagates to the rest of the activation loop, resulting in intramolecular docking of the HPD motif onto the kinase C lobe and completion of the P+1 pocket, thus providing the full complement of interactions required to facilitate phosphotransfer to polypeptide substrates (23,35). Accordingly, pS172-activated TBK1 can quickly catalyze the modification of other TBK1 molecules, likely constituting the second rapid phase observed in TBK1 autoactivation reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Such highly coordinated interactions likely reduce the mobility of the loop compared with its unmodified state and can only be achieved by a phosphorylated residue, perhaps explaining why the TBK1 S172E phosphomimetic mutant shows decreased activity compared with the wild-type enzyme (20). The conformational change nucleated by the phosphorylation of S172 further propagates to the rest of the activation loop, resulting in intramolecular docking of the HPD motif onto the kinase C lobe and completion of the P+1 pocket, thus providing the full complement of interactions required to facilitate phosphotransfer to polypeptide substrates (23,35). Accordingly, pS172-activated TBK1 can quickly catalyze the modification of other TBK1 molecules, likely constituting the second rapid phase observed in TBK1 autoactivation reactions.…”
Section: Discussionmentioning
confidence: 99%
“…The structure of the OSR1 kinase domain, as determined by crystallography, revealed that OSR1 is capable of forming dimers, likely as a part of the kinase activation process (34). Structural elements in OSR1 that are involved in dimerization are also found in SPAK, raising the possibility that SPAK and OSR1 form heterodimers.…”
Section: Discussionmentioning
confidence: 99%
“…Domain swapping for the isolated kinase domains of cell cycle checkpoint kinase 2, death-associated protein kinase 3, lymphocyte-oriented kinase, and Ste20-like kinase has been proposed as a possible mechanism of trans-auto phosphorylation at non-consensus sites (25,26). More recently, domain swapping has been observed for the isolated OSR1 kinase domain, which in contrast to cell cycle checkpoint kinase 2, death-associated protein kinase 3, lymphocyte-oriented kinase, and Ste20-like kinase, does not undergo autophosphorylation (27). Autophosphorylation has not been observed for p70S6KD.…”
Section: Discussionmentioning
confidence: 99%